45 Maximising recruitment to clinical trials in hospices- experience of a multicentre study using the 'social marketing mix framework'. Issue 3 (1st September 2018) - White, Clare; Noble, Simon; Watson, Max; Swan, Flavia; Johnson, Miriam
Abstract : Introduction: Research in specialist palliative care units (SPCUs) has traditionally been considered difficult and studies are limited with poor recruitment and high attrition rates making interpretation of results challenging. Aims: To analyse recruitment from a UK multisite study in 5 SPCUs which recruited above target and compare recruitment strategies with recommendations from the 'Social Marketing Mix Framework' (SMMF) and learn lessons for future research in SPCUs. Methods: Recruitment data from the HIDDen (Hospice Inpatient DVT Detection) Study was analysed and compared with SMMF recommendations for improving recruitment to trials in palliative care. Results: Over 17 months 1390 patients with cancer were screened for HIDDen study inclusion in five SPCUs (three in N. Ireland, one in England and one in Wales) 797 (57%) patients were ineligible. 206 (35% of those eligible) declined participation with 387 (65% of those eligible) recruited. When compared with the '6Ps' of SMMF the study protocol addressed 'Participants' with broad study eligibility criteria 'Product' by replicating clinical practice with no change to routine clinical care and no competing trials 'Price' through minimising patient and carer burden and easing the consent process 'Place' by being done in patients own room in the SPCU and using five sites 'Promoting' through role play and maintaining the research profile and 'Partners' by addressing gatekeeping and minimising input from clinical staff by having on-site research staff. Discussion: Good recruitment to trials is possible in a SPCU setting and use of the '6Ps' of SMMF can help in trial design and recruitment. Reference: . Dunleavy L, Walshe C, Oriani A, Preston N. Using the 'social marketing mix framework' to explore recruitment barriers and facilitators in palliative care randomised controlled trials? A narrative synthesis review. Palliative Medicine 2018;32(5):990–1009. doi:10.1177/0269216318757623